2018
DOI: 10.1111/clr.13387
|View full text |Cite
|
Sign up to set email alerts
|

Variation in bucco‐palatal maxillary sinus width does not permit a meaningful sinus classification

Abstract: Objectives The bucco‐palatal sinus width (SW) appears as relevant factor for graft consolidation after maxillary sinus (MS) floor augmentation. The present study aimed to assess (a) SW at different height levels of posterior teeth, (b) possible factors influencing SW, and (c) whether a simple/meaningful sinus classification based on SW is possible. Methods The following parameters were recorded on computed tomographies of 76 edentulous and 86 partially edentulous maxillary quadrants displaying 383 tooth sites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
(38 reference statements)
1
9
0
Order By: Relevance
“…Regarding the different areas of the jaws, the outcomes of our study show a continuous increase in RW from anterior to posterior areas of both the dentate maxilla and mandible. This finding is in accordance with other studies, both in dentate [ 46 , 58 ] and in edentulous jaws [ 35 , 40 , 50 , 54 ]. A similar trend was shown for BW and PW/LW, as in [ 31 , 49 ], which clearly outlines and support the importance of defining different areas of the jaws .…”
Section: Discussionsupporting
confidence: 94%
“…Regarding the different areas of the jaws, the outcomes of our study show a continuous increase in RW from anterior to posterior areas of both the dentate maxilla and mandible. This finding is in accordance with other studies, both in dentate [ 46 , 58 ] and in edentulous jaws [ 35 , 40 , 50 , 54 ]. A similar trend was shown for BW and PW/LW, as in [ 31 , 49 ], which clearly outlines and support the importance of defining different areas of the jaws .…”
Section: Discussionsupporting
confidence: 94%
“…The included studies presented to some extent opposing results and conclusions drawn from the results of the present systematic review and meta-analysis should therefore be interpreted with caution. Moreover, histomorphometric outcomes after MSFA are influences by various confounding factors including sinus cavity dimensions, size of the lateral window, barrier membrane coverage of the lateral window, and retrievement of bone cores for histomorphometric analysis at different locations [58][59][60][61]. Varying degree of heterogeneity according to these parameters were present among the included studies [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45].…”
Section: Journal Of Oral and Maxillofacial Researchmentioning
confidence: 99%
“…Our main results revealed that there was a significant medial drop that accounted for 42% of the augmentation height and that sinuses wider than 15mm had statistically significantly higher medial and lateral drops than narrower sinuses. Zeng et al found a positive correlation between wide sinuses and high (linear height) bone graft resorption, and their explanation was related to the vascular supply [22]. From an anatomical point of view, if denuded from soft tissue, the main blood supply to the grafted material may be from the medial bony wall, which is nourished by the posterior lateral nasal artery.…”
Section: Discussionmentioning
confidence: 99%
“…Other sources of vascular supply are the posterior alveolar artery and the infraorbital artery on the lateral wall [19]. Zeng and his colleagues assumed that in wide sinuses, the blood supply is inadequate, resulting in higher bone resorption in comparison to narrow sinuses, where the intimate blood supply from the close walls enhances angiogenesis and graft remodeling [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation